Postharvest biology and technology of horticultural crops : principles and practices for quality maintenance - Siddiqui, Mohammed Wasim (AAP, Apple Academic Press, 2015)
The ultimate goal of crop production is to provide quality produce to consumers at reasonable rates. Most fresh produce is highly perishable, and postharvest losses are significant under the present methods of management in many countries. However, significant achievements have been made during the last few years to curtail postharvest losses in fresh produce and to ensure food security and safety as well. These include advancements in breeding horticultural crops for quality improvement; postharvest physiology; postharvest pathology and entomology; postharvest management of fruits, vegetables.
Keywords: Horticultural crops -- Postharvest technology.; Horticultural crops -- Biotechnology.; elektronické knihy; electronic books